Pertumbuhan, Produksi dan Efi siensi Pemanfaatan Lahan dalam Sistem Tumpangsari Jagung dan Kacang Hijau dengan Interval Penyiraman Berbeda - Laode Sabaruddin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
Water availability is a limiting factor to develop farming systems in the arid region, therefore more attention is given in the effort to increase water use true intercropping system. The research aim was to increase the productivity and land use effi ciency. Research was conducted at fi eld station of Agriculture Faculty, Haluoleo University. The experimental was arranged in completely randomized block design with two factors and three replications. The fi rst factor was watering interval, i.e. once every 2, 4 and 6 days. Second factor is planting time of mungbean, i.e. 0, 7, 14, 21 and 28 days after planting (DAP) maize. The result showed that total yield of maize is 5.67 ton ha-1 in intercropping system occurred at delayed planting of mungbean, i.e. at 14 DAP maize, and watering interval every 4 days. Our result showed that intercropping system could improve yield up to 39.68% compared to monoculture planting system of maize and mungbean. Leaf area index, long ear and number of grain per ear of maize have correlation with yield. Number of pod per hill of mungbean has correlation to weight of 1,000 grain and dry pod yield. Percentage of pod emptiness has negative correlation to weight of 1,000 grain and dry pods yield. Keywords: intercropping, LER, maize, mungbean, water availability